2022
DOI: 10.36740/wlek202208205
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Fatigue in Patients With Episodic Migraine

Abstract: The aim: We studied prevalence, intensity and predictors of fatigue in patient with episodic migraine (EM). Materials and methods: We enrolled in the study 85 patients with EM and 88 healthy subjects. Fatigue was identified according to Fatigue Severity Scale. We recorded socio-demographic factors: gender, age, marital status, formal education level, employment status, smoking. Anxiety and depression symptoms were assessed by Hospital Anxiety and Depression Scale, daytime sleepiness was measured by Epworth sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The prevalence of dementia in the first 3–6 months after a stroke ranges from 5 to 32% and after 12 months from 8 to 26%. The highest risk of developing poststroke cognitive disorders is observed during the first months after a stroke, which is probably due to previously unrecognized and undiagnosed initial manifestations of cognitive disorders [ 23 ]. In our study, cognitive impairment was found in almost half of the patients on the first day of ischemic stroke, and there was no significant reduction in this prevalence over 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of dementia in the first 3–6 months after a stroke ranges from 5 to 32% and after 12 months from 8 to 26%. The highest risk of developing poststroke cognitive disorders is observed during the first months after a stroke, which is probably due to previously unrecognized and undiagnosed initial manifestations of cognitive disorders [ 23 ]. In our study, cognitive impairment was found in almost half of the patients on the first day of ischemic stroke, and there was no significant reduction in this prevalence over 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Primary fatigue is a direct consequence of the disease, while secondary fatigue is a consequence of reduced functional capabilities, chronic pain, and treatment side effects. It may be defined as a decrease in physical and/or mental performance [ 124 ]. Nevertheless, the present literature clearly reports that the definition of patients with fatigue often depends on the type of scale used and it might not represent the actual experience of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…This study is subject to several limitations: (1) medications commonly prescribed for stroke patients, including sedatives, antiepileptics, pain medications, and antidepressants, may independently contribute to fatigue and may be differentially prescribed between ischemic and hemorrhagic strokes; (2) exclusion of patients unable to communicate their symptomatology, such as those with aphasia or altered states of consciousness ( 10 , 26–28 ); (3) other conditioning factors, such as neuroanatomical/biological aspects and unexamined comorbidities, likely influence the effects of fatigue on functional outcomes, particularly the lack of improvement in fatigue despite neurorehabilitation in ischemic strokes ( 15–17 , 19 , 28 ). Our data confirm the evolution of poststroke fatigue and associated factors reported elsewhere ( 25 , 29–31 ).…”
Section: Study Limitationsmentioning
confidence: 99%